(untitled) (Journal of Economic Research & Business Administration, 2015)
To ensure sustainable economic growth in the long term we need approaches to the definition of prioritisation criteria and methods for determining development priorities in the framework of the listed criteria, certain quantitative and qualitative assessments of the prospects of the whole economy up to branches, regions and their impact on the economic system. In General terms the criteria for selection of priority areas, which covers integration, the author proposes to consider the participation of the country in the world, provided by the growth of competitiveness and structural reorganization, creating belonging to the prospective growth points. Growth point for any socio-economic subsystem is the most important element, which ensures the growth of the system as a whole. On this basis, the priorities in the integration policy of the Republic of Kazakhstan is characterized by the following: • 1 vector – Kazakhstan’s participation in the CES • 2 vector – the desire to join WTO • 3 vector – integration in the SCO • 4 vector – integration of the Republic of Kazakhstan implemented within the framework of the CIS